Human Xq28 inversion polymorphism: From sex linkage to Genomics ‐ A genetic mother lode. Issue 2 (9th March 2016) - Kirby, Cait S.; Kolber, Natalie; Salih Almohaidi, Asmaa M.; Bierwert, Lou Ann; Saunders, Lori; Williams, Steven; Merritt, Robert
Abstract: An inversion polymorphism of the filamin and emerin genes at the tip of the long arm of the human X‐chromosome serves as the basis of an investigative laboratory in which students learn something new about their own genomes. Long, nearly identical inverted repeats flanking the filamin and emerin genes illustrate how repetitive elements can lead to alterations in genome structure (inversions) through nonallelic homologous recombination. The near identity of the inverted repeats is an example of concerted evolution through gene conversion. While the laboratory in its entirety is designed for college level genetics courses, portions of the laboratory are appropriate for courses at other levels. Because the polymorphism is on the X‐chromosome, the laboratory can be used in introductory biology courses to enhance understanding of sex‐linkage and to test for Hardy‐Weinberg equilibrium in females. More advanced topics, such as chromosome interference, the molecular model for recombination, and inversion heterozygosity suppression of recombination can be explored in upper‐level genetics and evolution courses. DNA isolation, restriction digests, ligation, long PCR, and iPCR provide experience with techniques in molecular biology. This investigative laboratory weaves together topics stretching from molecular genetics to cytogenetics and sex‐linkage, population genetics and evolutionary genetics. © 2016 by The International Union of Biochemistry and Molecular Biology, 44:191–201, 2016.